Effects of Changes in the Levels of Damage-Associated Molecular Patterns Following Continuous Veno–Venous Hemofiltration Therapy on Outcomes in Acute Kidney Injury Patients With Sepsis - Wu, Jie; Ren, Jianan; Liu, Qinjie; Hu, Qiongyuan; Wu, Xiuwen; Wang, Gefei; Hong, Zhiwu; Ren, Huajian; Li, Jieshou (Frontiers in Immunology, 2019)
Background: Continuous veno–venous hemofiltration (CVVH) could influence immunomodulation by cytokine removal. Damage-associated molecular patterns (DAMPs) are released by injured cells and have roles in sepsis. We investigated if the magnitude of DAMPs removal was associated with mortality in patients with sepsis undergoing CVVH. Methods: We conducted a prospective, observational study on patients acquiring CVVH at department of surgery, Jinling Hospital. Circulating levels of DAMPs (mitochondrial DNA [mtDNA]; nuclear DNA [nDNA]; heat shock protein [HSP]70) and cytokines were measured at the beginning, 6 h and 12 h of CVVH at the dialyzer inlet and outlet. Urinary DNA levels were analyzed at the beginning and end of CVVH. Human leukocyte antigen-DR (HLA-DR) expression was assayed at 0, 3, 7 days after CVVH initiation. Multivariable logistic regression analysis were performed to identify independent predictors of sepsis motility. Results: We evaluated 43 acute kidney injury (AKI) patients, 33 with sepsis and 10 without sepsis. 22 sepsis patients (67%) and three non-sepsis patients (30%) died (P = 0.046). Significant reduction in circulating IL-6 (P = 0.046) and TNF-α (P = 0.008) was found in the septic AKI group. mtDNA levels were increased (ND2, P = 0.035; D-loop, P = 0.003) and HSP70 level was reduced (P = 0.000) in all patients. Circulating levels of mtDNA and nDNA were increased dramatically after blood passed through the filter in septic AKI patients who survived. HSP70 clearance had good prediction efficiency for mortality (AUC = 0.937, P = 0.000). The HLA-DR level was increased upon higher clearance of HSP70 (P = 0.006). Higher HSP70 clearance was a significant independent predictor of mortality (OR = 1.025, 95% CI: 1.012–1.039, P = 0.000). The urinary nDNA level (β-globin) before CVVH was an independent risk factor for CVVH duration in AKI patient with sepsis (sRE = 0.460, 95% CI: 1.720–8.857, P = 0.005). Conclusion: Survival decreases significantly in higher HSP70 clearance rate. CVVH can not only remove the inflammatory factors and reduce the urinary DAMPs, but also remove beneficial molecules, and the removal of these beneficial molecules are associated with poor prognosis.